Michał z Damietty, "Nomokanon" 47, 9: "O modlitwach i uczęszczaniu do kościoła" - Nieuważny, Adam; Piwowarczyk, Przemysław (Vox Patrum, 2024)
The article contains an introduction and a commented translation of chapter 47.9 from the Nomocanon by Michael of Damietta.